Correlates of property crime in a cohort of recently released prisoners with a history of injecting drug use - Kirwan, Amy (Harm Reduct J, 2015)
BACKGROUND: Injecting drug use (IDU) is a strong predictor of recidivism and re-incarceration in ex-prisoners. Although the links between drug use and crime are well documented, studies examining post-release criminal activity and re-incarceration risk among ex-prisoners with a history of IDU are limited. We aimed to explore factors associated with property crime among people with a history of IDU recently released from prison. METHOD: Individuals with a history of IDU released from prison within the past month were recruited via targeted and snowball sampling methods from street drug markets and services for people who inject drugs (PWID) into a 6-month cohort study. A multivariate logistic regression analysis of baseline data identified adjusted associations with self-reported property crime soon after release. RESULTS: Interviews were conducted a median of 23 days post-release with 141 participants. Twenty-eight percent reported property crime in this period and 85 % had injected drugs since release. Twenty-three percent reported injecting at least daily. Reporting daily injecting (adjusted odds ratio (aOR) 4.36; 95 % confidence interval (CI) = 1.45–13.07), illicit benzodiazepine use (aOR = 2.59; 95 % CI = 1.02–5.67), being arrested (aOR = 6.12; 95 % CI = 1.83–20.45) and contact with mental health services (aOR = 4.27; 95 % CI = 1.45–12.60) since release were associated with property crime. CONCLUSION: Criminal activity soon after release was common in this sample of PWID, underscoring the need for improved pre-release, transitional and post-release drug use dependence and prevention programmes. Addressing co-occurring mental disorder and poly-pharmaceutical misuse among those with a history of IDU in prison, and during the transition to the community, may reduce property crime in this group.